FOREIGN EXPERIENCE OF MANAGING NATURAL MONOPOLY ENTERPRISES - Umarova Irodakhon Nuraliyevna (Journal of Contemporary Business Law & Technology: Cyber Law, Blockchain, and Legal Innovations, 2024)
This scientific article covers the experiences of foreign countries in managing natural monopoly enterprises. In particular, the existence and development of natural monopolies, mainly their interaction with the external environment, including determining the efficiency of the natural monopoly subject and comparing it with the alternative efficiency of the competitive market, the causes of market defects, market participants and types of activities Problems related to this are theoretically studied and methods of state regulation of natural monopoly enterprises are justified